On the boundary behavior of imbeddings of metric spaces into a Euclidean space - Salimov, R. R. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We investigate the boundary behavior of so-called Q-homeomorphisms with respect to a measure in some metric spaces. We formulate a series of conditions for the function Q(x) and the boundary of the domain under which any Q-homeomorphism with respect to a measure admits a continuous extension to a boundary point.